Organisational Culture in Polish Small Private Enterprises as an Inspiration for the Public Sector - Pyrzyńska, Ewa; Kudełka, Wanda (Journal of Public Governance, 2024)
Objective: This study seeks to identify and adapt elements of organisational culture from small enterprises in the apparel industry that can strengthen the functioning of public institutions. The objective is to provide guidelines for improving efficiency, ethics, and adaptability in organisations such as universities and the police, where formal structures alone are insufficient to meet the demands of the dynamic socioeconomic environment. Research Design & Methods: The study employed semi-structured in-depth interviews with owners, directors, and managers from micro and small enterprises in the Polish apparel industry, allowing for the collection of detailed qualitative data on organisational culture. The collected data was analysed thematically, enabling the recognition of recurring patterns in the respondents’ answers. Findings: The analysis revealed practices such as participatory management, trust-based relations, and openness to innovation, which, although rooted in the private sector, can serve as inspiration for enhancing the organisational culture of public institutions. Implications / Recommendations: The findings indicate that cultivating humanistic values, strengthening transparent communication, and integrating modern technologies can significantly improve the effectiveness and adaptability of public sector institutions. Such practices can foster employee trust, organisational efficiency, and broader social engagement. Contribution / Value Added: This study contributes to both academia and practice by applying elements of organisational culture from small enterprises in the apparel industry as a benchmark. Article classification: research article JEL classification: M14